2011
DOI: 10.1021/jz2011308
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Stabilized Rh Adatoms: 0D Oxides on a Vicinal Surface

Abstract: We have investigated the initial oxidation of the Rh(113) and Rh( 223) vicinal surfaces by STM and ab initio simulations. Upon adsorption of small amounts of oxygen, the surface morphology is completely altered. Surprisingly, oxygen-stabilized Rh adatoms can be observed on the (113) facets, with oxide-like electronic properties. We present models of these "0D oxide" phases and discuss reasons for their stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The reason for the shifted rows now becomes clear, since without the shifted rows some of the oxygen atoms would have occupied unfavorable bridgelike sites. However, it was recently shown that oxygen may stabilize Rh adatoms on a Rh(113) surface, 20 and we cannot exclude such a scenario on the Pd(113) nanofacets. Therefore, we propose a model as shown in Fig.…”
Section: B Low-pressure Regime: Chemisorption On Pd(112)mentioning
confidence: 83%
“…The reason for the shifted rows now becomes clear, since without the shifted rows some of the oxygen atoms would have occupied unfavorable bridgelike sites. However, it was recently shown that oxygen may stabilize Rh adatoms on a Rh(113) surface, 20 and we cannot exclude such a scenario on the Pd(113) nanofacets. Therefore, we propose a model as shown in Fig.…”
Section: B Low-pressure Regime: Chemisorption On Pd(112)mentioning
confidence: 83%
“…On ultrathin FeO films, to reach a Pd density somewhere in between that on ZrO 2 /Pt 3 Zr and ZrO 2 /Pd 3 Zr, the deposition temperature has to be decreased to 130 K . The reason becomes clear when studying the bonding geometries: For the late transition metals, bonding to two atoms at opposite sides is favorable. Assuming typical Me–O bond lengths around 0.2 nm, an O–Me–O geometry requires O–O distances of ≈0.4 nm with space in between for the Me atom. This is possible at open surfaces like the distorted ZrO 2 {111} variants (Figure ), but not on most other oxides with in-plane O–O distances typically around 0.30 nm or less.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum is widely used as a catalyst in numerous chemical reactions. It plays an important role as a heterogeneous catalyst in hydrogenation and dehydrogenation reactions, for example, and platinum is a vital component of automotive three-way catalytic converters. Despite the importance of platinum in catalysis, there have been only a very limited number of spectroscopic studies of its clusters in the gas phase. , It is well-known that the oxidation state of a metal catalyst’s surface strongly affects its catalytic behavior; according to several reports in the literature, oxidized Pt, Pd, Rh, and PtRh surfaces are more efficient during the catalytic oxidation of CO than the pure metal surfaces. The reaction mechanisms of CO and NO oxidation are not well understood at the molecular level, however, and thus more information concerning the reactivity of catalytically active metals such as Pt is clearly needed.…”
Section: Introductionmentioning
confidence: 99%